Por un fundamento ético-jurídico de la participación diferenciada de los pueblos indígenas en las decisiones estatales - Cerqueira, Daniel (Pontificia Universidad Católica del Perú, 2015)
Within the Latin American state Constitutions, is the establishment of prior consultation for theindigenous peoples legitimate? Does it represent away of imposition of the minority rights in front ofthe majority rights? Does it implies a power of vetoover the state decisions?In this article, the author answers the aforementioned questions, as he assays an ethical and legal foundation for the establishment of the mechanism of free, prior and informed consultation, one that goes beyond its national and international recognition.

Dentro de las Constituciones de América Latina,¿es legítimo el establecimiento de la consulta previa a los pueblos indígenas? ¿Supone una imposición de los derechos de las minorías frente a losderechos de las mayorías? ¿Implica un poder de veto de las decisiones estatales?En este artículo, el autor responde a estas inte- rrogantes mientras ensaya un fundamento jurídico y ético para el establecimiento del mecanismo de la consulta previa, libre e informada, que vaya más allá de su reconocimiento nacional e internacional.
Towards an ethical and legal foundation of the differentiated participation of the indigenous peoples in the State decisions
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01